Pengaruh Penggunaan Tepung Jangkrik (Gryllus Sp.) Pada Ransum Ayam Kokok Balenggek Terhadap Konsumsi Protein, Energi Dan Rasio Efisiensi Protein - Anisa, Anisa; Ali Akbar, Syahro; Astuti, Tri (Jurnal Peternakan Mahaputra, 2023)
The Balenggek crowing chicken is a local (native) breed from West Sumatra, specifically found in the PayungSekaki District, Solok Regency. Known for their melodious, cascading crowing sound, these chickens areclassified as singing chickens. They are commonly found in areas bordering forests and around rice fields.The aim of this research was to investigate the effect of incorporating cricket flour into the diet of BalenggekCockerels over a 12-week period on protein consumption, energy consumption, and protein efficiency ratio.The research design employed in this study was an experimental method utilizing a Completely RandomizedDesign (CRD) with 4 treatments and 4 replications. Each experimental unit consisted of 48 IMR males with bodyweights ranging from 254.47 to 464.73 grams. The treatments included: P0: Without the use of cricket flour P1:Use of 2% cricket flour, P2: Use of 4% cricket flour, P3: Use of 6% cricket flour, The parameters measuredincluded protein consumption, energy consumption, and protein efficiency ratio. The results of the study indicatedthat the inclusion of cricket flour had a highly significant effect (P<0.01) on protein onsumption, energyconsumption, and protein efficiency ratio in the diet of Balenggek crowing chickens. The best outcomes wereobserved with the use of 6% cricket flour, which led to a significant increase in protein consumption, energyconsumption, and protein efficiency ratio.